(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This paper examines current innovative pedagogical technologies in English language teaching, analyzing existing challenges and modern approaches to addressing them. The research focuses on theoretical frameworks and practical implementations of technology-enhanced learning methods, highlighting their effectiveness in improving English language acquisition.